Knowledge of Women about the Early Detection Methods of Cervical Cancer in Baghdad City (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Cervical Cancer is considering a public health problem, leading cause of mortality andmorbidity among women.Objective: To assess women’s knowledge regarding cervical cancer and. early detection methodsMethodology: A descriptive study was conducted, included (200) women from different levels of educationwho work in the institute, from 5th November 2018 to 30 April 2019, by using interview technique and selfreporting technique . A non-probability (purposive) sample of (200) women. The questionnaire was usedfor data collection. The validity was estimated through a penal of experts related to the field of study, and sous the reliability was evaluated through a pilot study conduct included (10) women (except from the originalsample). Data is analyst through the implementation of descriptive and inferential statistical analysis.Results: The results of this study show that the knowledge of the study sample was low regarding earlydetection methods, prevention treatment and there was statistical significant relationship between level ofknowledge, and some variablesRecommendations: It was recommended that increase coverage in cervical screening programs from Iraqministry of health to encourage women in Iraq. In addition, training program should supply in educationalinstitute
Keywords: Cervical Cancer, Knowledge Pap Smear and Women